Strategies for enhancing social skills of individuals with intellectual disability: A systematic review - Jacob, Udeme Samuel; Edozie, Isioma Sitamalife; Pillay, Jace (Frontiers in Rehabilitation Sciences, 2022)
Individuals with intellectual disability who suffer from comorbid mental health problems are likely to experience difficulties in socialising. Deficits in social skills are also associated with challenging behaviours and self-injury. This paper presents global evidence from a systematic review of literature on such issues as ‘interventions’; ‘social skills development’, and ‘individuals with intellectual disability’. A thorough search of various bibliographic databases identified 1 124 academic papers. Ten papers met the inclusion criteria for in-depth analysis concerning the use of interventions to develop social skills among individuals with intellectual disability. The study revealed that the social skills of individuals with intellectual disability had been fostered using different strategies, such as classroom‑based intervention, emotional intelligence training, use of a peer network intervention, computer games of emotion regulation, and puppet play therapy. Furthermore, the findings suggest that various aspects like communication, bridging the gap in social skills deficits, emotional recognition and regulation, and adaptive behaviour were fostered using the identified intervention strategy. This review revealed that social skills interventions appeared modestly effective but may not be generalisable to school settings or self-reported social behaviour for individuals with intellectual disability. It is also necessary to increase the sample size in future studies to draw generalisable conclusions.